Effectiveness Of Differential Pjbl Model On Student Learning Results Of Sd Students On Deforestation Materials - Nurbaidah, Ririn; Tukiman Hendrawijaya, Arief; Wicaksono, Iwan (ATTA`DIB, 2025)
This study aims to examine the effect of the Differentiated Project-Based Learning (PjBL) model on elementary school students’ learning achievement in the topic of deforestation within the subject of Science and Social Studies (IPAS). The research employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group. The participants were 47 upper-grade students, 27 Student from SDN Rowotengah 03 and 20 student SDN Rowotengah 04 in Jember Regency. The experimental group (27 students) was taught using the differentiated PjBL model, while the control group (20 students) received conventional instruction. Instruments included a rubric-based observation for a multiple-choice test for learning outcomes. Descriptive analysis showed that the experimental group had higher learning achievement (82.75) compared to the control group (71.43 and 70.91, respectively). Independent sample t-tests revealed significant differences between the groups for variables (p < 0.05). These results indicate that the implementation of the differentiated PjBL model has a significant positive impact on improving elementary students’ social-emotional skills and academic achievement.